Strategi Pengembangan Profesionalisme Guru - Miramadhani, Avicni; Putri, Apriliany; Faelasup, Faelasup (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
This research aims to identify and describe various strategies for developing teacher professionalism that can be applied in various educational contexts. Teacher professionalism is very important in improving the quality of education, because teachers have a strategic role in developing students' potential. The challenges faced by teachers are increasingly complex with stechnological developments, curriculum changes, and society's demands for educational outcomes. This research uses a library research approach to analyze relevant theories and concepts. Research findings show that teacher professional development involves various aspects, including pedagogical competence, content knowledge, and educational technology capabilities. Effective professional development strategies will help teachers improve their competence, strengthen commitment, and motivate them in carrying out their duties. Thus, developing teacher professionalism is the main key in creating an effective and quality education system in Indonesia.